PISANGAUL LAMPUNG: INOVASI DIGITAL AGROSOCIOPRENEURSHIP BERBASIS PEMANFAATAN POTENSI TANAMAN PISANG DI DESA SUMUR SEBAGAI SENTRA OLEH-OLEH KHAS LAMPUNG - Piz Roni; Putri Indriyanti; Desrita Pratiwi; Maringan Simamora; Erina Nurhidayah; Sumargono Sumargono (BUGUH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
South Lampung Regency is one of the largest banana producers in Lampung province. One of the districts that is the largest banana-producing industrial center in South Lampung Regency is Sumur Village, Ketapang District. Sumur Village has good banana plantation potential, but utilization into processed products has not been carried out optimally. Usually bananas are directly sold to the market in a raw state. This can cause a lack of development of residents' creativity in utilizing resources and cause the economic value obtained by the community in the village to be less than optimal. Based on these problems, the PKM PisanGaul team held assistance in processing bananas into banana chips, banana brownies, banana ice cream, banana heart nugets and crackers from pisanng weevils, The mentoring activities carried out aim to open new insights of the community and also build an entrepreneurial spirit. The target of this community service is mothers in Sumur Village. In the implementation of this activity using two methods, namely socialization and training methods. After the training program was carried out, PKM partner participants consisting of PKK mothers and the general public of Sumur Village, had begun to be skilled in carrying out banana plant processing techniques into derivative products. So based on the Community Service activities that have been carried out with the title Pisangaul Lampung Digital Innovation of Agrosociopreneurship based on the utilization of the potential of banana plants in Sumur Village as a typical souvenir center of Lampung, it can be concluded that this training activity can: Improve the knowledge and skills of PKK mothers and the general public of Sumur Village in the field of processing and utilizing banana plants into various derivative products that have high selling value. Not only that, in this activity, direct sales of training products have also been carried out to several tourist attractions in the area and also through social media (Instagram) and websites that we have developed previously so that products processed by the people of Sumur Village are expected to be known by all people in Indonesia.